2009
DOI: 10.1103/physrevb.79.125401
|View full text |Cite
|
Sign up to set email alerts
|

Quantum site percolation on triangular lattice and the integer quantum Hall effect

Abstract: Generic classical electron motion in a strong perpendicular magnetic field and random potential reduces to the bond percolation on a square lattice. Here we point out that for certain smooth 2D potentials with 120 • rotational symmetry this problem reduces to the site percolation on a triangular lattice. We use this observation to develop an approximate analytical description of the integer quantum Hall transition. For this purpose we devise a quantum generalization of the real-space renormalization group (RG)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
0
20
2
Order By: Relevance
“…In this chapter we describe two network models proposed recently: the first one is a weakly chiral network p − q model, 26 27 constructed to study the levitation of extended states at low magnetic fields, and the second one is a triangular model, 28 proposed as an alternative to the quadratic CC model to describe inter-plateaux transitions in the IQHE. It was later generalized 27 to study the levitation scenario as p − q model.…”
Section: Weakly Chiral and Triangular Network Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this chapter we describe two network models proposed recently: the first one is a weakly chiral network p − q model, 26 27 constructed to study the levitation of extended states at low magnetic fields, and the second one is a triangular model, 28 proposed as an alternative to the quadratic CC model to describe inter-plateaux transitions in the IQHE. It was later generalized 27 to study the levitation scenario as p − q model.…”
Section: Weakly Chiral and Triangular Network Modelsmentioning
confidence: 99%
“…In Ref. [28] the critical exponent of the triangular model was inferred from the real space renormalization group analysis ≈ 2 3 ÷ 2 76. Later, in Ref.…”
Section: Weakly Chiral and Triangular Network Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 76 it was demonstrated that these probabilities are equal to 4/9. Correspondingly, the probability of the forward scattering is 1/9.…”
Section: A Fully Chiral Triangular Modelmentioning
confidence: 99%
“…While for the square p-q model each chiral network was of CC type, here each chiral network represents a "triangular" model introduced in Ref. 76 …”
Section: Triangular P-q Modelmentioning
confidence: 99%